Preparation of Z-substituted styrenes using hiyama and suzuki cross couplings: a synthesis of glandulone B - Engles, Courtney A. (Western Washington University, 2011)
The heliannuols are a family of allelochemicals that have been isolated from the common sunflower (Helianthus annuus). The 8-membered cyclic ether moiety found in many of the heliannuols is a rare motif in nature and provides a challenging synthetic target. It has been found that conformational constraint in the form of a Z olefin helps promote the cyclization of aryl epoxides to the 8-membered cyclic ether. Hiyama couplings of aryl iodides and cyclic vinyl siloxanes produce Z-styrenes in good to excellent yields. Due to the expense of the catalyst used for the synthesis of the siloxanes, an alternate pathway to the Z olefins utilizing vinyl cyclic boronic half acids was also pursued, but was ultimately unsuccessful. Due to the success of Hiyama couplings, the synthesis of glandulone B was pursued. The dimethoxyhydroquinone derivative of glandulone B was synthesized from an aryl iodide and cyclic vinyl siloxane in a 23% yield over 4 steps. Oxidation of the dimethoxyhydroquinone to glandulone B was explored.